Variables associated with grief and personal growth following the death of a child from cancer: A mixed method analysis. Issue 9 (21st October 2021) - Donovan, Leigh A.; Wakefield, Claire E.; Russell, Vera; Fardell, Joanna; Mallitt, Kylie-Ann; Hetherington, Kate; Cohn, Richard
Abstract: This mixed method study explored parent and child characteristics that impact grief and personal growth in parents ( n  = 119) after a child dies from cancer in Australia. Medical components of a child's cancer care including radiation treatment, referral to palliative care, and location of death had a significant impact on levels of grief. Parents' gender, religious affiliation, and education level had a significant impact on levels of personal growth. This study further enhances our understanding of the impact of specific parent and child characteristics throughout a child's cancer treatment and end of life that may influence their families' experience of bereavement.